ASSESSMENT OF STUDENT LEARNING THROUGH THE USE OF SEMI-CONTEXTUALIZED MEASURES IN MEDELLIN - Clara Amador-Lankster; Marlen Monsalve Orrego; Alexander Rincon Silva (European Scientific Journal, ESJ, 2015)
The purpose of this article is to present a 2014 Fulbright proposed evaluation framework and to analyze recent findings resulting from the administration of contextual measures anchored on local instructional practices of LEARNING BY DOING and academic standards from the National Education Ministry in Colombia in the areas of Mathematics, Language & Literacy and Inquiry-Based Learning. The goal of the Fulbright grant funded project was to explore, examine and analyze the structure, scope and extent of implementation of the ALIANZA MODEL (Learning by Doing) in five municipalities situated in the southwest region of Medellin in Colombia, in order to propose an Evaluation Framework to measure the extent of implementation and level of educational effectiveness in the region. The ALIANZA MODEL was originally designed to improve the quality of education for students attending designated public schools in grades K -11, with the goal to bridge and close the academic achievement gap within the region. The specific objectives of the ALIANZA MODEL were defined: 1) Facilitating and enhancing learning in mathematics, language arts and investigation as pedagogical strategy; 2) Contributing to the improvement of the processes of educational management and cultural transformation of public schools; 3) Creating inter-municipal networks to strengthen actions for the improvement of quality and equity of education in the region; 4) Strengthening the confidence of both private and public sectors in the implementation of public education policies; and 5) Strengthening Professional Development Models of teachers so that they would have a positive and effective impact on students learning.